2020
DOI: 10.3390/ijerph17030979
|View full text |Cite
|
Sign up to set email alerts
|

Secondhand Smoke Exposure in Public Places and Support for Smoke-Free Laws in Japan: Findings from the 2018 ITC Japan Survey

Abstract: Comprehensive smoke-free policies such as those called for by the WHO FCTC are the only way to protect the public effectively from the harms of secondhand smoke (SHS), yet Japan has been slow to implement this important health measure. This study examines baseline levels of smoking and SHS exposure in public places and support for smoking bans in Japan prior to the implementation of the 2018 national smoke-free law. Data are from the International Tobacco Control (ITC) Japan Wave 1 Survey (Feb–Mar 2018), a web… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…First, a substantially higher percentage of concurrent NVP-cigarette users stated that they used NVPs because they could use them in places where smoking cigarettes is banned (63.1% among males, 64.3% among females) vs. concurrent HTP-cigarette users in Japan (49.4%). This may be due to the presence of strong and enforced smoke-free laws in those four countries, which would highlight the perceived benefits of vaping, relative to the weak and weakly enforced smoke-free laws in Japan [31]. Second, concurrent NVP-cigarette users were much more likely to cite saving money as a reason for using NVPs (64.7% among males, 64.9% among females) vs. concurrent HTP-cigarette users in Japan (20.3%), reflecting both the relatively lower cost of vaping vs. smoking in the four countries and the nearly equal cost of using HTPs vs. smoking in Japan and elsewhere [30], and the overall marketing and positioning of HTPs as a high-end product [28,32].…”
Section: Discussionmentioning
confidence: 99%
“…First, a substantially higher percentage of concurrent NVP-cigarette users stated that they used NVPs because they could use them in places where smoking cigarettes is banned (63.1% among males, 64.3% among females) vs. concurrent HTP-cigarette users in Japan (49.4%). This may be due to the presence of strong and enforced smoke-free laws in those four countries, which would highlight the perceived benefits of vaping, relative to the weak and weakly enforced smoke-free laws in Japan [31]. Second, concurrent NVP-cigarette users were much more likely to cite saving money as a reason for using NVPs (64.7% among males, 64.9% among females) vs. concurrent HTP-cigarette users in Japan (20.3%), reflecting both the relatively lower cost of vaping vs. smoking in the four countries and the nearly equal cost of using HTPs vs. smoking in Japan and elsewhere [30], and the overall marketing and positioning of HTPs as a high-end product [28,32].…”
Section: Discussionmentioning
confidence: 99%
“…If game players were to leave in the middle of a game to go outside to smoke for a prolonged time, it would influence the results of the game. Previous studies conducted in settings similar to these also reported that smoking bans in indoor public places could protect customers and workers from SHS [4,23]. Obviously, SFLs can protect SHS, but its effects have not always been consistent.…”
Section: Discussionmentioning
confidence: 85%
“…In the Kyoto cohort (TFH-PTCL), a similar situation might apply. In Japan, a recent study showed that the overall prevalence of SHS exposure in workplaces, restaurants, and bars were 49, 55, and 83% ( Sansone et al, 2020 ). These data may partially explain the accumulation of COSMIC Signature 4-like driver mutations in the non-smokers.…”
Section: Discussionmentioning
confidence: 99%